(untitled) - Paul K Anderson (Boston, Massachusetts, 1997)
The book covers the basics of the Unix operating system. It has eight main parts. Part I gives an overview of the Unix operating system. Part II organizes information in collection called files. Part III interprets user commands and passes them on to the computer called shell. Part IV discusses the most popular Unix editor called vi ("vee-eye"). Part V presents Internet and Web tools. Part VI examines startup files. Part VII describes a program for the Unix shell called shell scripts. Finally, Part VIII discusses the programming languages C, Fortran, and Pascal
Keywords: computer networks,operating systems ( computers ),unix ( computer file )